Effect of Varying Solvents on Structural Properties of Annealed PVDF-Trfe Thin Films - N. Arshad, A.; N. Sarip, M.; N. Sarip, M.; Z. Engku Zaharah, E.; D. Rozana, M. (International Journal of Engineering and Technology, 2019)
PVDF-TrFE (70:30 mol%) powders were dissolved individually in three polar solvents of Diethyl Carbonate (DEC), Methyl Ethyl Ketone (MEK) and N-, N-, Dimethylformamide (DMF). The solution was spin coated and formed PVDF-TrFE films of 250 nm thickness; UN DEC, UN MEK and UN DMF films. Â PVDF-TrFE powders were found to readily dissolve in DMF solvent as indicated by Hansen solubility parameters (Î´t). Hansen parameter showed small difference in reading (Î´t = 1.7) forÂ PVDF-TrFE and DMF, and low relative energy difference (RED) value. All films were annealed at 120Â°C (AN DEC, AN MEK, AN DMF). The AN DMF film showed high presence of polar Î²-phase crystals as evident from the ATR-FTIR spectrum. This is given by the significant peaks at 848, 1190, and 1290 cm-1. The trend is consistent with XRD pattern, where relative increment of cps value (53%) at 19.2Â° (2Î¸) is observed. This further supports the high degree of Î²-phase crystals observed in AN DMF film.Â Â